HUBUNGAN PERANTI ORTODONTI CEKAT TERHADAP KESEHATAN JARINGAN PERIODONTAL - Kornialia, Kornialia (Jurnal Endurance, 2018)
Orthodontic treatment, especially with fixed orthodontic appliances is aimed at improving facial aesthetics, tooth structure and for obtaining good static occlusion and function relationships. But the disadvantages that are often caused mainly the health problems of periodontal tissues such as the occurrence of gingivitis and periodontitis. Periodontal disorders associated with fixed orthodontic treatment are due to plaque retention, orthodontic band irritation, archwire or ligature and the influence of orthodontic pressure itself. This study aims to determine the relationship of periodontal tissue health to users of fixed devices with those who do not use the appliance. The type of this research is analytic survey research with cross sectional approach. The research was conducted at Dental and Orthology Hospital of Baiturrahmah University Dentistry Faculty which was held from April to November 2010. The subject of this research is the co-ass student of Dentistry Faculty of Baiturrahmah University. Subjects were randomly picked as many as 30 people who were using fixed orthodontic appliances and 30 people without using devices. Data was collected from the Russell Index checks. Chy-Square analysis showed that there was a significant correlation between users of fixed orthodontic appliances with those not using devices on their periodontal tissue health (p value = 0.002). So it is concluded that users of fixed appliances of periodontal tissue health are worse than those who do not use fixed appliances. Perawatan ortodonti terutama dengan peranti ortodonti cekat adalah bertujuan untuk memperbaiki estetika wajah, susunan gigi geligi serta untuk mendapatkan hubungan oklusi statis dan fungsi yang baik. Namun kerugian yang sering ditimbulkannya adalah terutama masalah kesehatan jaringan periodontal seperti terjadinya gingivitis dan periodontitis. Kelainan-kelainan periodontal yang berhubungan dengan perawatan ortodonti cekat disebabkan oleh adanya retensi plak, iritasi band ortodonti, archwire atau ligature serta pengaruh tekanan ortodonti itu sendiri. Penelitian ini bertujuan untuk mengetahui hubungan kesehatan jaringan periodontal pada pemakai peranti cekat dengan yang tidak memakai peranti. Jenis penelitian ini adalah penelitian survei analitik dengan pendekatan cross sectional. Penelitian dilaksanakan di Rumah Sakit Gigi dan Mulut Fakultas Kedokteran Gigi Universitas Baiturrahmah yang dilaksanakan pada bulan April s/d November 2010. Subjek penelitian adalah  mahasiswa co-ass  Fakultas Kedokteran Gigi Universitas Baiturrahmah. Subjek diambil secara acak sederhana sebanyak 30 orang yang sedang memakai peranti  ortodonti cekat dan 30 orang tanpa memakai peranti. Data dikumpul dari  pemeriksaan Indeks Russel. Analisis Chy-Square menunjukkan bahwa terdapat hubungan yang signifikan antara pemakai peranti ortodonti cekat dengan yang tidak memakai peranti terhadap kesehatan jaringan periodontalnya (p value = 0,002). Sehingga disimpulkan bahwa pemakai peranti cekat kesehatan jaringan periodontalnya lebih buruk dari yang tidak memakai peranti cekat.